A Catalog of Distance Determinations for 5 Million Stars in LAMOST DR10 - Chengqun Yang; Xiang-Xiang Xue; Chao Liu; Hao Tian; Ling Zhu; Lan Zhang (The Astronomical Journal)
Using the distance estimation method outlined in J. L. Carlin et al., a Bayesian approach specifically tailored for LAMOST data, we estimated distances for 7,450,303 spectra from 5,394,174 unique stars in the LAMOST DR10 low-resolution data set. To accommodate the significant increase in data volume and quality in LAMOST DR10, several improvements were applied to the method in J. L. Carlin et al.: utilizing denser isochrones, increasing the density of interpolated isochrone grids, and incorporating Gaia G -band magnitudes alongside Two Micron All Sky Survey K -band magnitudes for more comprehensive distance estimates. A comparison with Gaia parallaxes shows good consistency across the data. For parallaxes below 1 mas, the estimated distances are underestimated by 4% for the K band and 10% for the G band, while for parallaxes below 0.25 mas, the distances are overestimated by 9% for the K band and 7% for the G band. Distance uncertainties initially increase with distance, with relative distance uncertainties starting at 5% at 1 kpc and rising to 17% at 20 kpc, then decreasing to 10%–15% for distances greater than 50 kpc. The number of stars with distances between 5 and 10 kpc is ∼1.8 × 10 ^5 , and ∼6 × 10 ^4 for distances greater than 10 kpc.